Unsteady MHD 2- liquid heat transmission plasma flow in a rotating system with Hall Currents via permeable conducting plates - Raju, Linga T.; Venkata Rao, Bonu (Zielona Góra: Uniwersytet Zielonogórski)
A theoretical study is conducted on an unstable magneto hydrodynamic two-phase heat transfer plasma flow within a horizontal channel, which is bounded by conducting and permeable plates. The analysis takes place in a rotating frame of reference and includes the effect of Hall current. The regular perturbation approach determines the governing differential equations under the adopted conditions. The velocity and thermal distribution are visually resolved, and a parametric study is executed. Two fluid flow and heat transmission factors are affected by governing characteristics like as the porosity parameter, Hall parameter, Hartmann number, Taylor`s number, height, electrical, viscosity, and thermal conductivity ratios.
Keywords: heat transfer; immiscible flow; rotating frame; Hall effect; conductive porous plates; perturbation method